Advances in network clustering and blockmodeling - Doreian, Patrick; Batagelj, Vladimir 1948-; Ferligoj, Anuška (John Wiley & Sons, 2020)
"This book provides an integrated treatment of network clustering and blockmodeling (the most frequently used technique in social network analysis). There are many approaches that have been developed for partitioning networks across multiple disciplines such as: community detection, blockmodeling of valued networks, role assignment, stochastic blockmodeling, etc. This book will include a wide variety of new techniques addressing these problems with a view to solving them. Presented in a comprehensive manner, this book will provide the foundations for understanding network structures and processes. New approaches and methods that have been developed in the last 10 years in the field of both network clustering and blockmodeling will be the main focus of this book"--
Includes bibliographical references and indexes. - Online resource; title from digital title page (viewed on January 23, 2020)
Keywords: Social networks -- Mathematical models; Sociometry; Réseaux sociaux; Modèles mathématiques; Sociométrie; Social networks; Mathematical models